Exposure : Canadian Contemporary Photographers. (Toronto : Art Gallery of Ontario, 1975)
Mavrides, Alkistis ; Butterfield, David ; Knottenbelt, Marianna ; Heywood, J.C. ; Emre ; Abraham, Michael ; Miller, Margo ; Gaudard, Pierre ; Brooks, Robert ; Abbott, Louise ; Semaja ; Tonn, Harry ; Thomas, Peter ; Schreier, Michael ; Hohn, Hubert ; Parker, Craig ; etc.
Exposure: Canadian Contemporary Photographers / Exposure: Photographes Canadiens Contemporains, Art Gallery of Ontario, Toronto, November 1, to November 27, 1975
English-French
kunstcatalogus
Keywords: Canada